2019
DOI: 10.1111/myc.12984
|View full text |Cite
|
Sign up to set email alerts
|

Acute‐subacute paracoccidioidomycosis: A paediatric cohort of 141 patients, exploring clinical characteristics, laboratorial analysis and developing a non‐survival predictor

Abstract: Summary The acute‐subacute form of paracoccidioidomycosis (PCM) is a severe systemic mycosis that affects children and adolescents from endemic regions, leading to generalised lymphadenopathy, fever, weight loss, anaemia, eosinophilia, hypoalbuminemia and hypergammaglobulinemia. The objective of this study is to describe the clinical and laboratorial characteristics of acute‐subacute PCM, to determine a mortality risk factor and to propose a test for non‐survival hazard related to the disease. Children and ado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 45 publications
(187 reference statements)
0
4
0
Order By: Relevance
“…Before puberty, PCM (disease) tends to affect both sexes more closely. This is well illustrated in the study by Romaneli et al, which showed that, in children up to 12 y/o, the male-to-female ratio was 1.5:1, while male predominance started in children between 12 and 15 y/o (7:1) [4]. In studies of large cohorts consisting predominantly of adults, women corresponded to less than 5% of the cases [5][6][7][8].…”
Section: Introductionmentioning
confidence: 61%
“…Before puberty, PCM (disease) tends to affect both sexes more closely. This is well illustrated in the study by Romaneli et al, which showed that, in children up to 12 y/o, the male-to-female ratio was 1.5:1, while male predominance started in children between 12 and 15 y/o (7:1) [4]. In studies of large cohorts consisting predominantly of adults, women corresponded to less than 5% of the cases [5][6][7][8].…”
Section: Introductionmentioning
confidence: 61%
“…When comparing the two periods of the study, the proportion was similar (1.6% versus 1.9%), despite the increase in acute forms. This might be associated with a higher chance of dissemination due to a delay in diagnosis, since the acute form is rare and unknown by professionals in basic health units [ 10 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Deaths due to paracoccidioidomycosis are caused by extremely disseminated lesions, respiratory insufficiency, adrenal insufficiency and may occur a long time after antifungal treatment [50]. Romanelli et al [53] studying PCM in children in Campinas, Brazil, showed a relapse rate of 7.8%, renal insufficiency of 8.3% and a mortality of 5.7%, significantly associated with low serum albumin. Giusiano et al [55] reported an increase of juvenile PCM in Northeast Argentina, an area that suffered deforestation and a change in the agricultural practices, with soybean replacing cotton; one of the biggest hydroelectric dams in South America, Yacyret a, was constructed there.…”
Section: Andandmentioning
confidence: 99%
“…The acute–subacute form is usually observed in children and adolescents without epidemiological risk activities, corresponding to 5–25% of all PCM cases; sick infected children/adolescents have a T cell immune response which is inadequate to control the fungal infection [50,51 ▪ ]. PCM usually presents with fever, weight loss, multiple skin lesions, generalized lymphadenopathy with draining fistula from lymph nodes and hepatosplenomegaly [52,53] (Fig. 1).…”
Section: Paracoccidioidomycosismentioning
confidence: 99%